2021
DOI: 10.21873/invivo.12447
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity in Hypofractionated/Stereotactic Prostate Radiotherapy of Elderly Patients: Use of the Image-guided Radio Therapy (IGRT) Clarity System

Abstract: Background: The use of intra-fractional monitoring and correction of prostate position with the Image Guided Radio Therapy (IGRT) system can increase the spatial accuracy of dose delivery. Clarity is a system used for intrafraction prostate-motion management, it provides a real-time visualization of prostate with a transperineal ultrasound. The aim of this study was to evaluate the use of Clarity-IGRT on proper intrafraction alignment and monitoring, its impact on Planning Tumor Volume margin and on urinary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…In order to locate the tumor, in our case the prostate, and to check if its position changes during the treatment, some golden fiducials (usually four) are implanted in the prostate wall; the reconstruction of the prostate position by means of such markers allows adjustments of the accelerator real-time with respect to the target [ 17 , 18 , 19 ]. For the sake of completeness, in RT, when an accelerator is supported by an image system, the technology is called image guided radiotherapy (IGRT), and the use of accurate image guidance is crucial to minimize setup errors and facilitate the margins reduction between the gross tumor volume (GTV) and the Planning target volume (PTV), especially for SBRT.…”
Section: Methodsmentioning
confidence: 99%
“…In order to locate the tumor, in our case the prostate, and to check if its position changes during the treatment, some golden fiducials (usually four) are implanted in the prostate wall; the reconstruction of the prostate position by means of such markers allows adjustments of the accelerator real-time with respect to the target [ 17 , 18 , 19 ]. For the sake of completeness, in RT, when an accelerator is supported by an image system, the technology is called image guided radiotherapy (IGRT), and the use of accurate image guidance is crucial to minimize setup errors and facilitate the margins reduction between the gross tumor volume (GTV) and the Planning target volume (PTV), especially for SBRT.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that absorbable hydrogel spacers injected into the perirectal space could reduce adverse events not only in GI toxicities but also in GU toxicities and sexual function problems (34). It has also been suggested that the use of image-guided radiation therapy, which has been developed in recent years, may reduce toxicity in the treatment of elderly patients (35). Since such measures to reduce adverse effects are becoming available, there is no need to be reluctant to use RT because of the high incidence of Grade 2 adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…These results were achieved employing agility VMAT and IMRT techniques, which were assisted by high-efficiency treatments that reduced treatment time even while delivering a high dose per fraction. It was reported that using modern radiotherapy technologies to reduce treatment duration resulted in greater compliance by patients and mild toxicity (Franco et al 2021). Also, using Agility MLC during treatment may enhance patient comfort and reduce intra-fraction motion around organs.…”
Section: Discussionmentioning
confidence: 99%